2006
DOI: 10.1093/nar/gkl538
|View full text |Cite
|
Sign up to set email alerts
|

Sit down, relax and unwind: structural insights into RecQ helicase mechanisms

Abstract: Helicases are specialized molecular motors that separate duplex nucleic acids into single strands. The RecQ family of helicases functions at the interface of DNA replication, recombination and repair in bacterial and eukaryotic cells. They are key, multifunctional enzymes that have been linked to three human diseases: Bloom's, Werner's and Rothmund-Thomson's syndromes. This review summarizes recent studies that relate the structures of RecQ proteins to their biochemical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 77 publications
(106 reference statements)
1
53
0
Order By: Relevance
“…7 and 1a and 1b). The conserved sequence of some of the domains is slightly different and both of these proteins contain ATP binding and helicase C-terminal regions ( 42 In some RecQ proteins multiple HRDC domains are also present. 42 HRDC domain is an 80-amino acid domain usually found at the C-terminus of RecQ helicases and RNase D homologs from various organisms, including human, yeast and bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 and 1a and 1b). The conserved sequence of some of the domains is slightly different and both of these proteins contain ATP binding and helicase C-terminal regions ( 42 In some RecQ proteins multiple HRDC domains are also present. 42 HRDC domain is an 80-amino acid domain usually found at the C-terminus of RecQ helicases and RNase D homologs from various organisms, including human, yeast and bacteria.…”
mentioning
confidence: 99%
“…The conserved sequence of some of the domains is slightly different and both of these proteins contain ATP binding and helicase C-terminal regions ( 42 In some RecQ proteins multiple HRDC domains are also present. 42 HRDC domain is an 80-amino acid domain usually found at the C-terminus of RecQ helicases and RNase D homologs from various organisms, including human, yeast and bacteria. 43 This domain is involved in the binding of protein to specific DNA structures (e.g., long-forked duplexes and Holliday junctions) that are formed during replication, recombination or transcription.…”
mentioning
confidence: 99%
“…WRN has a modular composition (Fig. 6a) and structural studies on the protein's domains and those of homologues are helping to define WRN mediated functions (Killoran and Keck, 2006). The N-terminus of WRN contains the exonuclease domain, the central core contains the helicase region and in the C-terminus two regions have been identified that bind protein partners and/or DNA (Sharma et al, 2006).…”
Section: Double-strand Breaks Base Excision Repair and Wrnmentioning
confidence: 99%
“…This is similar to the Q motif in RNA DEAD-box helicases, indicating a possible evolutionary link between the two families. Mutations in the helicase motifs disrupt the function of RecQ helicases (Killoran and Keck, 2006). In WRN, a mutation in Motif I in mice induces a Werner phenotype in mice tail-derived fibroblasts (Wang et al, 2000).…”
Section: Double-strand Breaks Base Excision Repair and Wrnmentioning
confidence: 99%
“…RecQ family members have been found in diverse organisms, including bacteria, yeasts, fungi, flies, frogs, and humans. Prokaryotes and unicellular eukaryotes usually possess a single RecQ homologue, while multicellular organisms express multiple ones (4)(5)(6). In E. coli, RecQ[Ec] is the solitary RecQ helicase.…”
mentioning
confidence: 99%